Sexual Homicide of Children: A New Classification - Chopin, Julien; Beauregard, Eric (International journal of offender therapy and comparative criminology, 2019)
The sexual homicide of a child is an unusual event, and very few studies have been conducted on the topic. Previous studies have mainly focused on the differences between sexual homicide of child and adult victims. The current study aims to identify a typology of sexual homicide of children based on modus operandi, offenders’ and victims’ characteristics. Using two-step cluster analysis on a sample of 72 cases of extra familial sexual homicide of children (aged 16 years or below) from France, six clusters have been identified on the basis of eight modus operandi variables: intentional/prepubescent, inadvertent/prepubescent, intentional/preteen, inadvertent/preteen, indiscriminate/teen, and intentional/teen. External validity of the classification was tested using 51 additional variables related to victims, offenders, and other modus operandi characteristics. Findings showed that sexual homicide of children is a heterogeneous phenomenon, largely influenced by the actual age of the victim and the type of violence used. Implications of the findings are discussed considering prevention, criminal investigation, and correctional practices.